Possibilities of MRI in the Diagnosis of Lumbar Vertebral Stenosis - Toshtemirov O; Ablyazov A.A; Zulunov A.T (Zien Journals, 2023)
This article highlights work devoted to the study of the possibility of MRI in the diagnosis of lumbar spinal stenosis.
Keywords: MRI; tumor; protrusion; stenosis